Russian social media influence understanding Russian propaganda in Eastern Europe - Helmus, Todd C.; Bodine-Baron, Elizabeth; Radin, Andrew; Magnuson, Madeline; Mendelsohn, Joshua; Marcellino, William; Bega, Andriy; Winkelman, Zev (RAND Corporation, 2018)
"A RAND Corporation study examined Russian-language content on social media and the broader propaganda threat posed to the region of former Soviet states that include Estonia, Latvia, Lithuania, Ukraine, and, to a lesser extent, Moldova and Belarus. In addition to employing a state-funded multilingual television network, operating various Kremlin-supporting news websites, and working through several constellations of Russia-backed "civil society" organizations, Russia employs a sophisticated social media campaign that includes news tweets, nonattributed comments on web pages, troll and bot social media accounts, and fake hashtag and Twitter campaigns. Nowhere is this threat more tangible than in Ukraine, which has been an active propaganda battleground since the 2014 Ukrainian revolution. Other countries in the region look at Russia's actions and annexation of Crimea and recognize the need to pay careful attention to Russia's propaganda campaign. To conduct this study, RAND researchers employed a mixed-methods approach that used careful quantitative analysis of social media data to understand the scope of Russian social media campaigns combined with interviews with regional experts and U.S. and North Atlantic Treaty Organization security experts to understand the critical ingredients to countering this campaign."--Publisher's description.
Keywords: Geschichte 2011-2018; Information warfare -- Russia (Federation); Social media -- Russia (Federation); Propaganda, Russian -- Former Soviet republics; Propaganda, Russian -- Ukraine. Russia (Federation); Propaganda; Social Media; Russland; Osteuropa